Investigation on Internet addiction disorder in adolescents in Anhui, People’s Republic of China - Chen Y; Kang Y; Gong W; He L; Jin Y; Zhu X; Yao Y (Neuropsychiatric Disease and Treatment, 2016)
Yan Chen,1 Yaowen Kang,2 Weizhi Gong,3 Lianping He,1 Yuelong Jin,1 Xiaoyue Zhu,1 Yingshui Yao1 1School of Public Health, Wannan Medical College, Wuhu, Anhui, People’s Republic of China; 2Fushun Administrative College, Fushun, Liaoning, People’s Republic of China; 3Guangdong Polytechnic of Industry and Commerce, Guangzhou, People’s Republic of China Background and aim: The purpose of this study was to describe the characteristics and prevalence of Internet addiction (IA) in adolescents so as to provide a scientific basis for the communities, schools, and families.Methods: We conducted a survey by randomized cluster sampling on 5,249 students, grades ranging from 7 to 12, in Anhui province, People’s Republic of China. The questionnaire consisted of general information and IA test. Chi-square test was used to compare the status of IA disorder (IAD).Results: In our results, the overall detection rate of IAD and non-IAD in students was 8.7% (459/5,249) and 76.2% (4,000/5,249), respectively. The detection rate of IAD in males (12.3%) was higher than females (4.9%). The detection rate of IAD was statistically different between students from rural (8.2%) and urban (9.3%) areas, among students from different grades, between students from only-child families (9.5%) and non-only-child families (8.1%), and among students from different family types.Conclusion: Prevalence of IA is high among Chinese adolescents. IAD has more effect on male students, single-child families, single-parent families, and higher grade students. We should take more care of male students, only-child students, and students living with their fathers, and related education should be strengthen for susceptible subjects of IDA. Keywords: adolescents, addictive behavior, Internet, health surveys